Wave Makers: The Drama That Sparked #MeToo in Taiwan - Yixin Xu (Global Storytelling)
Wave Makers, a Netflix original Taiwanese TV series, has not only captivated audiences with its compelling narrative but also sparked the #MeToo movement in Taiwan. The drama, set against the backdrop of a presidential election, intertwines personal and political narratives. This review explores the show’s impact, its unique approach to political storytelling, and its role in promoting social reform through media, illustrating how it encourages victims to speak out and inspire a discussion on gender equality and social justice.